Práticas de uso da linguagem com o gênero discursivo regras de jogo: um trabalho com sequência didática para o aprimoramento da capacidade linguístico-discursiva - Esteves, Leliane Regina Ortega (2016)
Aiming to develop a contextualized practice in this research, we focused on the theme "Working with the speech genre Game Rules in reading and writing teaching," once we recognize genres as teaching and learning instruments, because we understand that they present the real conditions of socio-historical-ideological achievement of language. In this perspective, we try to answer to the following questions: could the work with the speech genre Game Rules contribute to the development of discursive competence in students of the 6th year, enabling them to interact in social practices that require the ability to injunctive language? A teaching procedure with this genre can help improve reading comprehension and also promote the production of written texts, so that they can instruct and lead the interlocutor towards the desired actions by the speaker? Considering these issues, we draw as general objective to reflect, through studies, development and implementation of a Didactic Sequence with the genre Game Rules, on the importance of working with speech genres in elementary school, specifically with students of the 6th year in perspective of developing the ability to instruct and prescribe actions by reading and textual production. The theoretical and methodological basis was anchored in the Dialogic Conception of Language (Bakhtin/Volochínov, 2009[1929]; Bakhtin, 2010[1079]), outlining possible approaches to the Social-discursive Interactionism represented by Bronckart (2012[1996]) and authors that dialogue with these two conceptions: Cristovão (2002); Dolz, Noverraz and Schneuwly (2004 [2001]); Costa-Hübes (2008, 2014) among others. The investigative process is thus located in Applied Linguistics, supported by interpretative qualitative approach, of ethnographic nature, once tried to reflect on the development of linguistic and discursive skills through the work with the Game Rules genre. In the data generation procedure, we adopted the following route: at first, we used the diagnostic research through interviews with Portuguese teachers language, analysis of textbook collections, survey applied to students, and activities exploring the genre in focus, for the purpose of verifying how the genres, and more specifically, Game Rules, is understood and worked at school. In the second phase, we expanded our knowledge of the Game Rules, through the development of a Didactic Model of the Genre in order to, from discoveries produced by this model, develop and implement a didactic sequence exploring the teachable content of this instrument for the improvement of language. On the third moment, we developed an action-research (TRIPP, 2005), taking as a starting point, the application of a didactic sequence in the selected class and analysis of the achieved results. As a result of this process, we verified the progress of the students in order to produce and present instructions in both reading and writing activities, and in interactions in the classroom and in the meeting with their families. Through reading activities, we found that students have appropriated of the thematic content, of the compositional construction and of the genre style Game Rules, in a satisfactory way, developing important reflections on their movement in society. The written productions demonstrated the student s theoretical and practical appropriation according to the genre in study and the social function of writing. The rewriting activities contributed to the student s reflection on the linguistic elements and perfected the materiality of their texts. Thus, working with the Game Rules genre put students in a real situation of discursive communication, as planned, and enabled them to increase their ability to instruct and prescribe actions and to read a text responsively.